2021
DOI: 10.3390/medicina57101022
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Body Mass Index to Muscular Viscoelastic Properties in Normal and Overweight Individuals

Abstract: Background: The body mass index (BMI) is closely related to fat tissue, which may have direct or indirect effects on muscle function. Previous studies have evaluated BMI and muscle viscoelastic properties in vivo in older people or individual sexes; however, the relationship between BMI and muscular viscoelastic properties is still unknown. Aims: The purpose of this study was to determine the correlation of BMI with muscular viscoelastic properties, and to compare these properties in a young sedentary populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Results from this research may inevitably limit the possibilities for generalization. It is widely acknowledged that strong athletes who specialize in collision sports generally have high body weight, and that body weight is usually considered to be one of the main factors related to changes in the shape of the arch [57]. All participants' BMI within this study exceeded the normal range.…”
Section: Discussionmentioning
confidence: 61%
“…Results from this research may inevitably limit the possibilities for generalization. It is widely acknowledged that strong athletes who specialize in collision sports generally have high body weight, and that body weight is usually considered to be one of the main factors related to changes in the shape of the arch [57]. All participants' BMI within this study exceeded the normal range.…”
Section: Discussionmentioning
confidence: 61%
“…This discrepancy can be accounted for by differences in weight and height, which can explain ∼50% of the variance in skeletal mass in men and women (Janssen et al, 2000). In this line, it has been shown that body mass index (BMI) is associated with greater MT (Sanz‐Paris et al, 2021) (Usgu et al, 2021); so the higher BMI of the subjects analyzed by Maganaris and Baltzopoulos could explain the slightly higher TA MT reported in their study. Another factor that could explain differences in MT between studies relies on the procedure used to measure TA.…”
Section: Discussionmentioning
confidence: 76%
“…As a higher BMI indicates a larger body size, it appears reasonable that BMI was positively correlated with muscle thickness. Regarding the relationship between BMI and muscle stiffness, a recent study employed a MyotonPRO device to assess biceps brachii and biceps femoris muscles and reported a positive correlation between BMI and muscle tonicity [ 34 ]. A possible explanation is that an increased BMI leads to escalated loading stimuli, further causing higher muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%